A simple score to select patients for manual thrombectomy in emergent percutaneous coronary interventions: the DDTA score. Issue 8 (August 2020) - Cordero, Alberto; Freites, Alfonso; Escribano, David; Bertomeu-Martínez, Vicente; Zuazola, Pilar; Badimon, Lina
Abstract : Background: The objective of manual thrombectomy is the removal of occlusive thrombus to improve the results of primary angioplasty. The better understanding of the factors associated with successful manual thrombectomy may provide relevant information regarding thrombus formation and resolution. Methods: Observational study of all consecutive patients remitted for emergent percutaneous coronary intervention (PCI) in a single centre. Successful manual thrombectomy was considered when TIMI 3 was achieved after using the device and a score to predict successful manual thrombectomy was designed. Results: We included 618 patients, 65.1% treated with manual thrombectomy. No relevant differences in clinical features or time delays were observed between patients treated with vs. without manual thrombectomy, but manual thrombectomy treated patients received more often dual antiplatelet treatment (DAPT) before PCI. Final TIMI flow 3 was achieved in most patients and more frequently in manual thrombectomy treated patients (94.8 vs. 86.6%; P < 0.01). The successful manual thrombectomy rate was 81.3% and it was higher in patients pretreated with DAPT (89.0 vs. 73.3%; P < 0.01). The time delay to first medical contact was not related to the final TIMI 3, but it was significantly and negatively related to successful manual thrombectomy. According to the multivariate analysis, we designed the DDTA score: DAPT pretreatment (2), delay less than 2 h (3) or 2–4 h (2), TIMI flow improvement after wiring the lesion (2) and age less than 55 years (3). Patients with DDTA score at least 4 had lower no-reflow, mortality and major cardiovascular complications incidence. Conclusion: The DDTA score (DAPT pretreatment, time delays, TIMI flow improvement after wiring the lesion and age) identifies patients who benefit mostly from manual thrombectomy.